Management recommendations to reduce cardiac risk in chronic epilepsy - Trudy D. Pang; Richard L. Verrier; Steven C. Schachter (Epilepsy & Behavior Reports)
Multifactorial lines of evidence in adults point to a critical linkage between chronic epilepsy and elevated risk for cardiovascular disease and premature cardiac death. Diverse pathophysiological processes appear to be involved that include accelerated atherosclerosis, myocardial infarction, abnormal autonomic tone, heart failure, atrial and ventricular arrhythmias, and hyperlipidemia. Seizure-induced surges in catecholamines and hypoxia may be conducive to cardiovascular damage and the Epileptic Heart condition. The current review provides a systematic strategy for clinical management to reduce risk for cardiovascular disease in adult patients with epilepsy. The proposed approach includes adherence to cardiovascular risk guidelines, incorporation of standard monitoring using electrocardiographic and echocardiographic markers, and regular assessment of plasma lipid profiles. Attention is drawn to the arrhythmogenic risks associated with antiseizure medications (ASMs) with sodium channel blocking properties that can disrupt cardiac conduction and repolarization and predispose to ventricular and atrial arrhythmias. Caution is warranted regarding the use of enzyme-inducing ASMs that can increase plasma lipid levels. The ultimate goals of the proposed management recommendations are to mitigate cardiac risk and reduce premature cardiac death in individuals with chronic epilepsy.